HUNTING RIGHTS IN POLAND - Daniłowicz, Witold (Review of European and Comparative Law, 2018)
Although hunting rights constitute the key element of Polish hunting law, so far they have not been subject to detailed analysis in legal writings devoted to the subject. This is most likely due to the fact, that the term itself is not used in the hunting legislation. The article fills this gap. It analyzes the legal nature of hunting rights under Polish law as well as examines legal issues most closely related to this legal institution, namely hunting preserve and hunting lease. Also analyzed is the ownership of game at large, game carcass, hunting trophies and shed antlers.